Effects of cigarette smoking on quinine pharmacokinetics in malaria. - Pukrittayakamee, S; Pitisuttithum, P; Zhang, H; Jantra, A; Wanwimolruk, S; White, N (2002)
OBJECTIVE: Quinine is an important antimalarial drug that is metabolised mainly by the hepatic mixed-function microsomal enzyme cytochrome P(450). Cigarette smoking in healthy volunteers has been reported to enhance quinine clearance. The present study evaluated the effects of smoking on quinine pharmacokinetics in patients with uncomplicated falciparum malaria treated with a 7-day course of oral quinine. Of 22 studied male patients, 10 were regular smokers and 12 were non-smokers. METHODS: All patients were treated with a 7-day oral regimen of quinine sulfate (10 mg salt/kg three times a day). Serial venous blood samples were taken for quinine levels before and during treatment at 12 h and 24 h and then daily until day 7. Plasma quinine and 3-hydroxyquinine concentrations were assayed using high-performance liquid chromatography. Quinine pharmacokinetics were evaluated using non-compartmental modelling. RESULTS: All patients recovered, and there were no significant differences in clinical responses or cure rates between the two studied groups ( P> or =0.32). The median (range) fever clearance time was 51 h (4-152 h) and mean (SD) parasite clearance time was 74+/-28 h. The overall median times to maximum concentrations of quinine and its main metabolite 3-hydroxyquinine were 1.5 days and 4.0 days, respectively. The maximum concentrations of quinine were approximately tenfold higher than 3-hydroxyquinine. There were no significant differences in any pharmacokinetic variables for the parent compound or metabolite between the two groups. The median area under the plasma drug concentration-time curve to day 7 (AUC(0-7)) of quinine in non-smokers was 67.0 micro g/ml/day and in smokers was 51.3 micro g/ml/day, and AUC(0-7) values of 3-hydroxyquinine were 6.2 micro g/ml/day and 4.8 micro g/ml/day, respectively. CONCLUSION: These results indicated that cigarette smoking has no significant effects on quinine pharmacokinetics or the therapeutic response in patients with falciparum malaria.